2012
DOI: 10.1164/rccm.201104-0660oc
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Causal Relationship between Allergic Sensitization and Rhinovirus Wheezing in Early Life

Abstract: Rationale: Aeroallergen sensitization and virus-induced wheezing are risk factors for asthma development during early childhood, but the temporal developmental sequence between them is incompletely understood. Objective: To define the developmental relationship between aeroallergen sensitization and virus-induced wheezing. Methods: A total of 285 children at high risk for allergic disease and asthma were followed prospectively from birth. The timing and etiology of viral respiratory wheezing illnesses were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
277
4
14

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(311 citation statements)
references
References 25 publications
16
277
4
14
Order By: Relevance
“…The synergistic nature of allergic sensitisation and viral infections in infants relative to the onset of obstructive airway diseases was also demonstrated in a clinical study [107], which showed that current wheeze and asthma at 5 years of age were associated with virus-induced acute respiratory illness in children who displayed early allergic sensitisation (⩾2 years of age) but was not observed in nonatopic patients or those sensitised later. Finally, a causal role for allergic sensitisation in favouring or leading to more severe HRV-induced illness is supported by a subsequent evaluation of the COAST study, showing that allergic sensitisation may precede HRV-associated wheezing and may lead to an increased risk of wheezing illness caused by HRV but not RSV [108], while neither HRV-nor RSV-induced wheeze increase the risk of subsequent allergic sensitisation [10,[105][106][107][108]. In agreement with these epidemiological data are the results of a study comparing the immune responses during acute asthma exacerbation and convalescence in children sensitised to house dust mite (HDM).…”
Section: Role Of Hrv In Wheezing/asthma Inception and Exacerbationmentioning
confidence: 91%
“…The synergistic nature of allergic sensitisation and viral infections in infants relative to the onset of obstructive airway diseases was also demonstrated in a clinical study [107], which showed that current wheeze and asthma at 5 years of age were associated with virus-induced acute respiratory illness in children who displayed early allergic sensitisation (⩾2 years of age) but was not observed in nonatopic patients or those sensitised later. Finally, a causal role for allergic sensitisation in favouring or leading to more severe HRV-induced illness is supported by a subsequent evaluation of the COAST study, showing that allergic sensitisation may precede HRV-associated wheezing and may lead to an increased risk of wheezing illness caused by HRV but not RSV [108], while neither HRV-nor RSV-induced wheeze increase the risk of subsequent allergic sensitisation [10,[105][106][107][108]. In agreement with these epidemiological data are the results of a study comparing the immune responses during acute asthma exacerbation and convalescence in children sensitised to house dust mite (HDM).…”
Section: Role Of Hrv In Wheezing/asthma Inception and Exacerbationmentioning
confidence: 91%
“…Synergistic interactions between allergic sensitisation and viral respiratory infections in early life appear to be important in exacerbating the risk [99]. Allergic sensitisation precedes wheezing illness induced by human rhinovirus (HRV) in children who subsequently develop asthma [100]; this typically occurs in children with a genetic predisposition [101]. Trials aimed at preventing the onset of asthma by avoiding contact with allergens have had conflicting results.…”
Section: Allergic Sensitisationmentioning
confidence: 99%
“…HRV infection usually causes only mild illness [127]. The authors of the Childhood Origins of Asthma (COAST) birth cohort study among 259 children with an atopic background showed that allergic sensitisation preceded HRV wheezing illness, arguing against a causative role for HRV in the inception of asthma [100]. However, HRV-associated wheezing illness has an even stronger relationship with impaired lung function and asthma at school age (6-8 years) than does RSV infection [128,129].…”
Section: Viral Respiratory Infectionsmentioning
confidence: 99%
“…Triggers of asthma development are likely to differ from triggers of exacerbations. Recent studies suggest that respiratory viruses, possibly (sub-types of) human rhinovirus in particular, may play a role in triggering the immune system, particularly in children who are already sensitised to allergens [37]. The mechanisms are currently not known but allergic sensitisation appears to be an important underlying feature of triggering disease development; although several hypotheses exist, including an immune circle in asthma development in which repeated airborne irritant stimuli (such as allergens or viruses) evoke cycles of inflammation giving intermittent inflammation resulting in episodic symptoms at first, later turning into more persistent inflammation and disease expression [16].…”
Section: Asthma Pathologymentioning
confidence: 99%